Rationally Designed DNA Nanostructures for Drug Delivery - Xu, Fan; Xia, Qing; Wang, Pengfei (Frontiers in Chemistry, 2020)
DNA is an excellent biological material that gets emerging attention in the field of nanotechnology due to its unique capability for precisely engineering materials via sequence specific interactions. Self-assembled DNA nanostructures of prescribed physicochemical properties have demonstrated potent drug delivery efficiency in vitro and in vivo. By using bioconjugation techniques, DNA nanostructures can be precisely integrated with various functional moieties such as targeting ligands, proteins, inorganic nanoparticles etc. to enrich their functionalities and to enhance their performance. In this review, we begin with strategies on constructing DNA nanostructures. Further, we summarize the biological barriers ahead of drug delivery using DNA nanostructures followed by introducing existing rational solutions to overcome these biological barriers. Lastly, we discuss challenges and opportunities for DNA nanostructures towards real applications in clinical settings.